Sistem Pendukung Keputusan Untuk Pemilihan Vendor IT Menggunakan Metode TOPSIS Pada PT IBBI - Zefri Andi; Mercy Hermawati (Jurnal Ilmu Komputer dan Sistem Informasi, 2026)
IT vendor selection is a strategic decision that affects service quality, cost efficiency, and the sustainability of a company’s information technology systems. PT Investasi Bangun Bangsa Indonesia (PT IBBI) faces challenges in its IT vendor selection process, which is still conducted manually and tends to be subjective, potentially leading to suboptimal decisions. This study aims to design and develop a web-based decision support system for IT vendor selection using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. The TOPSIS method is applied to support multi-criteria decision-making by ranking vendors based on their proximity to the positive ideal solution and their distance from the negative ideal solution. The criteria considered include price, service quality, implementation time, portfolio, reliability, and uptime. The research methodology includes system requirements analysis, a literature review, data collection through observation and interviews, system design, implementation of the TOPSIS algorithm, and system testing using black-box testing. The results indicate that the proposed system is capable of providing objective and measurable IT vendor recommendations. Therefore, this decision support system can enhance the effectiveness and efficiency of the IT vendor selection process at PT IBBI while minimizing the risk of decision-making errors.